Integration Of Ecotourism And Creative Economy In The Canvas Business Model In Tanjung Rejo Tourism Village - Dina Aprija; Dewi Yanti; Muhammad Khadry (Wonderful-Journal of Tourism Destination, 2026)
The utilization of mangrove ecotourism potential in Tanjung Rejo Tourism Village has not been optimal despite the support of abundant natural resources and local wisdom, thus necessitating an integrated business model with the natural‐dye batik creative economy. This study aims to evaluate that integration within the Business Model Canvas (BMC) framework and to formulate development strategies through SWOT analysis. The method employed is a case study with data collected via semi-structured interviews with community members, tourism stakeholders, batik artisans, and village officials during April–May 2025, participatory observation, and document review. The analysis maps the nine BMC building blocks and applies indicators of Strength (internal strengths: skilled human resources and mangrove potential), Opportunity (external opportunities: government policies and ecotourism market interest), Weakness (limitations in basic infrastructure and digital marketing capacity), and Threats (destination competition and climate change impacts). The results indicate that Tanjung Rejo Village falls into the SO quadrant, with five BMC blocks—particularly Value Propositions, Key Resources, and Customer Segments—already established, while Channels and Customer Relationships still  require  reinforcement.  The  study  concludes  that  the  integration  of  mangrove  ecotourism  and  the natural-dye batik creative economy is underway but not yet optimal, and it offers practical guidance for other tourism villages adopting a creative ecotourism-based BMC. Strategic recommendations include enhancing infrastructure, providing digital marketing training, developing integrated tour packages, and forming Tourism Awareness Groups (Pokdarwis) to strengthen community participation and sustain partnership.